Hypothalamic dopaminergic stimulation in cluster headache. (October 2013) - Lepper, Anne; Frese, Achim; Summ, Oliver; Nofer, Jerzy-Roch; Evers, Stefan
Background: Cluster headache is associated with structural abnormalities of the hypothalamus. We were interested in the association of cluster headache with endocrinological functional abnormalities. Therefore, we applied the apomorphine challenge test, which is a specific test of hypothalamic dopaminergic activation. Methods: We enrolled 13 patients with cluster headache outside the bout and without medication. They were stimulated with 0.005 mg/kg of body weight subcutaneous apomorphine hydrochloride. After 45 and 60 minutes, growth hormone (GH), prolactin and cortisol were measured. The test was also applied to 14 sex- and age-matched healthy control subjects. Results: There were significantly higher GH levels in healthy subjects as compared to cluster headache patients 45 minutes after injection (10.8 ± 10.8 versus 4.4 ± 7.4 ng/ml; p = 0.038). Only in cluster headache, the GH level after 60 minutes was not significantly different from the baseline. The levels of prolactin and cortisol did not show any significant differences between cluster headache patients and in healthy subjects. Discussion: Our data suggest that cluster headache is associated with an impaired dopaminergic stimulation. This finding supports the body of evidence that cluster headache is associated with a functional abnormality of the hypothalamus and that this association is a primary (i.e. idiopathic) and not a secondary phenomenon during the bout.